Impact on shareholder wealth from emerging-market acquirers taking over developed-market targets - Coutinho, Madalena Marques da Silva Dias (2020)
In the last two decades, emerging markets have gained ground in the global market of mergers and acquisitions and are expected to continue doing so. Although it is fairly common for developed-market firms to acquire developing-market targets, the other way around is still a relatively new phenomenon. As such, the stock markets behaviour towards announcements of such acquisitions is still an underdeveloped research area with ambiguous answers. The event study methodology was used to examine whether developing-market acquiring firms are able to create value for their shareholders when targeting developed-market firms and what are the drivers of value creation. The sample used consisted of 300 deals from acquirers of ten different developing countries from 2005 until the beginning of 2020. The results reveal that, on average, these transactions create value for the acquirer’s shareholders, and that hiring financial advisors contributes positively to value creation. The growth rate of the home country and being state-owned also contribute to value creation, but the firm size, belonging to the high-tech industry and paying all-cash, on the other hand, were found to have a statistically significant negative impact on the value created. Lastly, managerial implications were drawn as well as openings for future research.